How I Minimize Junior High School Students’ Speaking Anxiety in The Classroom During My Teaching Practicum Program: A Self-Study Research - Cindy Dewie Lestari (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
English language teachers are aware of the issue known as foreign language speaking anxiety. It might be difficult to determine whether a student's reluctance to communicate in the target language stems from a lack of motivation or nervousness. To understand the causes of speaking anxiety, it's important to define the broad term anxiety based on its symptoms. According to Horwitz et al. (1986) anxiety is a subjective experience of tension, apprehension, nervousness, and worry caused by arousal of the autonomic nervous system. Anxious foreign language learners may experience symptoms such as perspiration, palpitations, stress, forgetfulness, and difficulty with language learning (Yalçın, Ö, & İnceçay, V, 2014). Anxiety caused by communicating in English can be debilitating, influencing students' adaptability to the target environment and, ultimately, their achievement of educational goals. Teachers must help students lessen their speaking anxiety so that they are able to achieve their learning objectives. This study aims to examine how I minimize student speaking anxiety during my teaching practicum program. This research was conducted at junior high school in Jember using a self-study method. in this research, the instrument of the research is the researcher herself. I collected data by observation and writing a reflective journal. The strategy I employ in this research is Fujii (2015) strategy. Fujii (2015) proposes four strategies: cooperation with others, increasing student self-confidence, getting teacher assistance, and using less stressful teaching methods. These strategies are thought to lessen student anxiety. To alleviate pupils' language anxiety, both teachers and students must take several steps. The solutions offered in this study are mostly focused on what students may do to reduce their anxiety, but they also include advice for teachers. In a reflective journal, I wrote what I had done during my teaching practice. I used thematic analysis from Braun and Clarke (2021) to analyze my data. This analysis used one theme, namely How I minimize students' speaking anxiety, with four subthemes: 1) Cooperation with other 2) Increasing student’ self-confidence 3) Assistance from the teacher 4) Less-stressful teaching methods. I identified the themes by observing teaching as well as from suggestions and feedback from the tutor and my partner. The research results show how I can reduce students' speaking anxiety in the classroom. The findings of this study revealed that four strategies from Fujii 2015 can help students lessen their speaking anxiety. Teachers play a crucial role in motivating and assisting students to develop self-confidence. Students who are confident in themselves will have less anxiety. Building a more pleasant classroom atmosphere with a sense of humor will help students relax while learning activities. Making students work in groups also increases their involvement and interaction in the classroom. Furthermore, teachers play a crucial role in helping students overcome their speaking anxiety. Students who experience anxiety usually refer to those who lack confidence. Teachers must take an active role in developing students. self-confidence. A comfortable and safe classroom environment will also encourage students to learn without fear of making mistakes. The study's findings revealed that four strategies for reducing student anxiety may assist students with their speaking anxiety. It is expected that the results of this study can provide a significant contribution, particularly for English teachers and other researchers. Teachers should be more sensitive to the conditions of their students. It is also hoped that teachers can build a safer and more enjoyable classroom environment so that students can learn safely and comfortably and will not be afraid to take risks in learning. Further research can be done using different strategies in dealing with students' speaking anxiety.
Reuploud file repositori 5 maret 2026_Firli
Keywords: Speaking; Speaking Anxiety; Practicum Program; A Self-Study Research; Metode Pembalajaran